A graphene-based electrode material, its preparation method and application

Through the moisturizing treatment of oxide film and induction of flame plasma, a porous mesh graphene electrode material is formed, which solves the problem of poor conductivity, short service life, and difficulty production in existing technology. Electrical materials with high -ratio capacitors and long life.

CN118026155BActive Publication Date: 2025-01-24GUIZHOU EDUCATION UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410181325.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-18
Publication Date
2025-01-24
Estimated Expiration
2044-02-18

AI Technical Summary

Technical Problem

The existing preparation methods for supercapacitor electrode materials have problems such as poor conductivity, non-conductivity of the binder, damage to the morphology of the grinding, short service life, and difficulty in efficient and large-scale production of high-performance reduced graphene oxide.

Method used

After moisturizing the oxide membrane, the flame plasma is induced to induce treatment to form a porous grid graphene -based electrode material. This method is simple and efficient, suitable for large -scale production, and improves the electrochemical performance of electrode materials.

Benefits of technology

The prepared graphene-based electrode material has high specific capacitance, long cycle life and good conductivity. It is suitable for supercapacitors and significantly improves the energy storage capacity and electrochemical activity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118026155B_ABST
    Figure CN118026155B_ABST
Patent Text Reader

Abstract

The present invention provides a graphene-based electrode material and a preparation method and application thereof, belonging to the technical field of electrode materials. The present invention uses flame plasma induction treatment on a wet graphene oxide film, and uses the hydrogen bonding between water molecules and oxygen-containing functional groups in graphite oxide to control the interaction between graphene oxide sheets, so that the graphene oxide film will not be fully stripped into sheets of reduced graphene oxide by the gas generated by decomposition during the flame plasma induced decomposition process, but instead forms a reduced graphene oxide porous mesh film. The method provided by the present invention is simple to operate, low in consumption, and highly efficient, and can be applied to the large-scale preparation of reduced graphene oxide porous mesh film materials. In addition, since the prepared electrode material has a porous network structure, it can effectively improve the capacity of the graphene-based electrode material, and the prepared material has good conductivity, and is used for supercapacitors with high specific capacitance and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a graphene-based electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, with the increasing demand for new energy mobile devices, the demand for fast-charging new energy storage devices with high power density, high energy density and long service life has also increased. Among them, supercapacitors are considered to be a new energy storage device with great development potential due to their advantages of fast charging, high power and long service life. Graphene-based materials, especially reduced graphene oxide, are more widely used in the construction of supercapacitors because of their large specific surface area, high conductivity, and more defects and active sites.

[0003] At present, the traditional method of preparing supercapacitor electrodes is to grind reduced graphene oxide and a binder into a paste, and then press two pieces of nickel foam together. The disadvantages of this method are that the conductivity between graphene sheets is poor; the binder is not conductive and reduces the conductivity; the morphology of graphene is destroyed during grinding, which leads to a decrease in the performance of the electrode; during the charging and discharging process, the powdered reduced graphene oxide expands in volume during use due to irregular accumulation, significantly reducing its service life; and the weak interaction between the flakes of reduced graphene oxide makes it impossible to fully establish a conductive network, resulting in shedding and charge transfer being blocked, reducing its energy storage capacity.

[0004] In addition, the commonly used preparation methods of reduced graphene oxide are hydrothermal method, solvothermal method, high temperature thermal decomposition method, chemical reduction method, flame method and microwave method, etc. However, the existing methods have the problems of cumbersome and time-consuming preparation process, special equipment, inability to mass produce, toxic reaction reagents, high temperature and high pressure process, poor performance of reduced graphene oxide and high cost.

[0005] Therefore, there is still an urgent need to develop a method for preparing graphene-based electrode materials that is simple to operate, efficient, scalable, and has excellent electrochemical properties. Summary of the invention

[0006] The object of the present invention is to provide a graphene-based electrode material and a preparation method and application thereof. The preparation method provided by the present invention is simple to operate, efficient, and can be mass-produced, and the prepared electrode material has excellent electrochemical properties.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a graphene-based electrode material, comprising the following steps:

[0009] (1) Wetting the graphite oxide film to obtain a wet graphite oxide film;

[0010] (2) The wet graphite oxide film obtained in step (1) is treated by flame plasma induction to obtain a graphene-based electrode material.

[0011] Preferably, the oxygen atom content of the graphite oxide in the graphite oxide film in step (1) is 25 to 30 at.%.

[0012] Preferably, the thickness of the graphite oxide film in step (1) is 10 to 40 μm.

[0013] Preferably, the wetting treatment method in step (1) comprises: placing the graphite oxide film in a water vapor environment until the graphite oxide film absorbs water to saturation, thereby obtaining a wet graphite oxide film.

[0014] Preferably, the temperature of the water vapor environment is 25-50°C.

[0015] Preferably, the standing time is 0.5 to 5 hours.

[0016] Preferably, the method of flame plasma induction treatment in step (2) comprises: contacting the graphite oxide film with the outer flame of the flame.

[0017] Preferably, the contact time is less than 3 s.

[0018] The present invention also provides a graphene-based electrode material prepared by the preparation method described in the above technical solution, wherein the graphene-based electrode material has a porous network structure.

[0019] The present invention also provides the use of the graphene-based electrode material described in the above technical solution as a working electrode of a supercapacitor.

[0020] The present invention provides a method for preparing a graphene-based electrode material, comprising the following steps: wetting a graphite oxide film to obtain a wet graphite oxide film; and treating the wet graphite oxide film by flame plasma induction to obtain a graphene-based electrode material. The present invention first wets the graphite oxide film, which, on the one hand, changes the flexibility of the graphite oxide film, making the graphite oxide film flexible and foldable; on the other hand, water molecules can be intercalated into the interlayers of graphene oxide sheets in the graphite oxide through hydrogen bonding, changing the interaction between graphene oxide sheets; and, due to the large specific heat capacity of water, the presence of water molecules can well absorb part of the heat generated during the decomposition of graphene oxide sheets, cool the gas generated by the decomposition, reduce the expansion pressure of the gas, and thus weaken the decomposition gas's ability to peel off the reduced graphene oxide sheets. The present invention uses flame plasma induction treatment on a wet graphite oxide film, and utilizes the hydrogen bonding between water molecules in the wet graphite oxide and oxygen-containing functional groups in the graphite oxide to control the interaction between graphene oxide sheets, so that the graphene oxide film will not be fully stripped into flaky reduced graphene oxide by the gas generated by decomposition during the flame plasma induced decomposition process, but a porous mesh-like reduced graphene oxide film will be formed.

[0021] The method provided by the present invention is simple to operate, low in consumption, and highly efficient, and can be applied to the large-scale preparation of reduced graphene oxide porous mesh film materials. In addition, since the prepared electrode material has a porous network structure, it can effectively improve the capacity of the graphene-based electrode material, solving the problem that it is difficult to efficiently and large-scale produce high-performance reduced graphene oxide in the prior art. The prepared material has good electrical conductivity, and is used for supercapacitors with high specific capacitance and long cycle life. The results of the examples show that the graphene-based electrode material prepared by the present invention has the following characteristics: ① Ultra-high specific capacitance, 230 to 280F / g; ② Long cycle life, 10,000 cycles of capacity retention> 90%; ③ Good electrical conductivity, charge transfer impedance <1Ω. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is an optical photograph of the graphene-based electrode material prepared in Example 1 of the present invention;

[0023] Figure 2 This is a SEM image of the graphene-based electrode material prepared in Example 1 of the present invention;

[0024] Figure 3 This is the XPS spectrum of the graphene-based electrode material prepared in Example 1 of the present invention;

[0025] Figure 4 The Raman spectrum of the graphene-based electrode material prepared in Example 1 of the present invention;

[0026] Figure 5This is an optical photograph of the reduced graphene oxide powder electrode material prepared in Comparative Example 1 of the present invention;

[0027] Figure 6 This is a SEM image of the reduced graphene oxide powder electrode material prepared in Comparative Example 1 of the present invention;

[0028] Figure 7 This is the XPS spectrum of the reduced graphene oxide powder electrode material prepared in Comparative Example 1 of the present invention;

[0029] Figure 8 The Raman spectrum of the reduced graphene oxide powder electrode material prepared in Comparative Example 1 of the present invention;

[0030] Fig. 9 The GCD diagram of the graphene-based electrode material prepared in Example 1 of the present invention at a current density of 1 A / g;

[0031] Fig.10 The GCD diagram of the reduced graphene oxide powder electrode material prepared in Comparative Example 1 of the present invention at a current density of 1 A / g;

[0032] Fig.11 A comparison chart of the specific capacitance of the graphene-based electrode material prepared in Example 1 of the present invention and the reduced graphene oxide powder electrode material prepared in Comparative Example 1;

[0033] Fig.12 This is an EIS graph of the graphene-based electrode material prepared in Example 1 of the present invention;

[0034] Fig.13 This is an EIS graph of the reduced graphene oxide powder electrode material prepared in Comparative Example 1 of the present invention;

[0035] Fig.14 This is a comparison chart of the cycle life of the graphene-based electrode material prepared in Example 1 of the present invention and the reduced graphene oxide powder electrode material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing a graphene-based electrode material, comprising the following steps:

[0037] (1) Wetting the graphite oxide film to obtain a wet graphite oxide film;

[0038] (2) The wet graphite oxide film obtained in step (1) is treated by flame plasma induction to obtain a graphene-based electrode material.

[0039] The present invention performs a wetting treatment on the graphite oxide film to obtain a wet graphite oxide film.

[0040] In the present invention, the oxygen atom content of the graphite oxide in the graphite oxide film is preferably 25 to 30 at.%, more preferably 28 to 30 at.%. In the present invention, the thickness of the graphite oxide film is preferably 10 to 40 μm, more preferably 10 to 20 μm. When the present invention uses the above-mentioned graphite oxide, there is a suitable hydrogen bonding effect between the oxygen-containing functional groups and the water molecules, which is more conducive to controlling the graphene-based electrode material to have a three-dimensional network structure.

[0041] The present invention has no special limitation on the method for preparing the graphite oxide film. A conventional method can be used to form a graphite oxide film of a desired thickness from graphite oxide.

[0042] The present invention has no special limitation on the preparation method of the graphite oxide, and it can be prepared by a conventional method. In the present invention, the preparation method of the graphite oxide is preferably the Hummers method, the Standenmaier method or the Brodie method.

[0043] In the present invention, the wetting treatment method preferably includes: placing the graphite oxide film in a water vapor environment until the graphite oxide film absorbs water to saturation to obtain a wet graphite oxide film. The present invention wets the graphite oxide film with water vapor, so that water molecules can fully enter between the graphite oxide film layers, fully wet the graphite oxide film, and will not cause the graphite oxide film to spread.

[0044] In the present invention, the temperature of the water vapor environment is preferably 25 to 50° C., more preferably 30 to 45° C. In the present invention, the standing time is preferably 0.5 to 5 hours, more preferably 0.5 to 3 hours. Under the above conditions, the present invention can fully wet the graphite oxide film.

[0045] The present invention has no special limitation on the device for forming the water vapor environment, and it is sufficient that the environment is filled with water vapor to moisten the graphite oxide film. In the present invention, the device for forming the water vapor environment is preferably a sealing groove with water distributed at the bottom. By adopting the above device, the present invention can form an environment filled with water vapor in the sealing groove through water evaporation.

[0046] After obtaining the wet graphite oxide film, the present invention uses flame plasma induction treatment on the wet graphite oxide film to obtain a graphene-based electrode material.

[0047] In the present invention, the method of flame plasma induction treatment includes: contacting the graphite oxide film with the outer flame of the flame.

[0048] In the present invention, the contact time is preferably less than 3 seconds. In the present invention, when the contact time is within the above range, the graphene oxide film will not be fully stripped into flaky reduced graphene oxide by the gas generated by decomposition during the flame plasma induced decomposition process, but a porous network of reduced graphene oxide film will be formed.

[0049] In the present invention, the flame preferably includes a flame generated by the combustion of ethanol, methanol or acetone. The present invention uses the flame generated by the above solvent as flame plasma, which can quickly induce the wet graphite oxide film to be fully reduced to reduced graphene oxide, and can utilize the hydrogen bonding between the water molecules in the wet graphite oxide film and the oxygen-containing functional groups in the graphite oxide film, so that the graphene oxide sheet will not be fully stripped into a sheet of reduced graphene oxide by the gas generated by the decomposition during the flame plasma induced decomposition, but will form a porous mesh-like reduced graphene oxide film.

[0050] The present invention uses flame plasma induction treatment on a wetted graphite oxide film, and utilizes the hydrogen bonding between water molecules in the wetted graphite oxide and oxygen-containing functional groups in the graphite oxide to control the interaction between graphene oxide sheets, so that the graphene oxide film will not be fully stripped into reduced graphene oxide sheets by the gas generated by decomposition during the flame plasma induced decomposition process, but a porous mesh-like reduced graphene oxide film is formed. The method provided by the present invention is simple to operate, low in consumption, and highly efficient, and can be applied to the large-scale preparation of reduced graphene oxide porous mesh-like film materials.

[0051] The present invention also provides a graphene-based electrode material prepared by the preparation method described in the above technical solution. In the present invention, the graphene-based electrode material has a porous network structure.

[0052] The present invention also provides the use of the graphene-based electrode material described in the above technical solution as a working electrode of a supercapacitor.

[0053] In the present invention, the method for using the graphene-based electrode material as a working electrode of a supercapacitor preferably includes: placing the graphene-based electrode material between two sheets of nickel foam and pressing to obtain a working electrode. The present invention has no particular limitation on the pressure and time of the pressing, which can be adjusted as needed. In the present invention, the pressing pressure is preferably 8 Mpa, and the pressing time is preferably 10 min.

[0054] Since the electrode material prepared in the present invention has a porous network structure, the capacity of the graphene-based electrode material can be effectively improved, and the problem in the prior art that it is difficult to efficiently and large-scale produce high-performance reduced graphene oxide is solved. The prepared material has good conductivity, high specific capacitance and long cycle life when used for supercapacitors.

[0055] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] Example 1

[0057] A method for preparing a graphene-based electrode material, comprising the following steps:

[0058] (1) Preparation of graphite oxide film by Hummers method in chemical exfoliation: 1 g of flake graphite and 0.5 g of sodium nitrate were weighed and placed in a 250 mL round-bottom flask, 23 mL of 98% by weight concentrated sulfuric acid was weighed and added to the round-bottom flask, a magnet was added, the round-bottom flask was placed in an ice-water bath, stirred for 30 min, 3 g of potassium permanganate was weighed and added to the reactor, and stirring was continued for 1 h. After the reaction was completed, the reactor was transferred to a 35°C water bath, and stirring was continued for 30 min. 5 0 mL of distilled water was added to the round-bottom flask, and then the round-bottom flask was transferred to an oil bath at 98° C. and stirred for 15 min. 140 mL of distilled water and 10 mL of 30% H2O2 were added in sequence. After the reaction system finally turned bright yellow, it was centrifuged, and then washed with 500 mL of 5% HCl and distilled water in sequence until the solution became neutral. The solution was then placed on the surface of a watch glass and dried to obtain a graphite oxide (oxygen atom content of 25 to 30 at.%) film with a thickness of 10 to 20 μm.

[0059] The prepared graphite oxide film was placed on the surface of a foam board floating on the water surface, the water temperature was maintained at 25°C, and the entire water tank was sealed with plastic wrap and left to stand for 3 hours to obtain a wet graphite oxide film;

[0060] (2) The wet graphite oxide film obtained in step (1) is subjected to flame plasma induction treatment, wherein the wet graphite oxide film is placed on the surface of a porous metal mesh and then moved into a flame zone. After the wet graphite oxide film changes from brown to black, the flame zone is immediately removed. The entire process takes less than 3 seconds to obtain a graphene-based electrode material.

[0061] Example 2

[0062] A method for preparing a graphene-based electrode material, comprising the following steps:

[0063] (1) Preparation of graphite oxide by the Standenmaier method in chemical exfoliation: 17.5 mL of concentrated sulfuric acid and 9 mL of concentrated nitric acid were weighed into a 250 mL flask and stirred for 15 min; 1 g of graphite was weighed and slowly added into the flask; after stirring, 11 g of potassium chlorate was added and reacted for 96 h; the graphite was washed with 800 mL of distilled water, then with 5% dilute hydrochloric acid, and finally with distilled water until neutral, and then placed on the surface of a watch glass and dried to obtain a graphite oxide (oxygen atom content of 25-30 at.%) film with a thickness of 10-20 μm;

[0064] The prepared graphite oxide film was placed on the surface of a foam board floating on the water surface, the water temperature was maintained at 50°C, and the entire water tank was sealed with plastic wrap and left to stand for 0.5 h to obtain a wet graphite oxide film;

[0065] (2) The wet graphite oxide film obtained in step (1) is subjected to flame plasma induction treatment, wherein the wet graphite oxide film is placed on the surface of a porous metal mesh and then moved into a flame zone. After the wet graphite oxide film changes from brown to black, the flame zone is immediately removed. The entire process takes less than 3 seconds to obtain a graphene-based electrode material.

[0066] Example 3

[0067] A method for preparing a graphene-based electrode material, comprising the following steps:

[0068] (1) Preparation of graphite oxide by the Hummers method of chemical exfoliation: 1 g of flake graphite and 0.5 g of sodium nitrate were weighed and placed in a 250 mL round-bottom flask, 23 mL of 98% by weight concentrated sulfuric acid was weighed and added to the round-bottom flask, a magnet was added, the round-bottom flask was placed in an ice-water bath, and stirred for 30 min, 3 g of potassium permanganate was weighed and added to the reactor, and stirring was continued for 1 h. After the reaction was completed, the reactor was transferred to a 35° C. water bath, and stirring was continued for 30 min. 50 mL of distilled water was added to the round-bottom flask, and then the round-bottom flask was transferred to an oil bath at 98°C and stirred for 15 minutes. 140 mL of distilled water and 10 mL of 30% H2O2 were added in sequence. After the reaction system finally turned bright yellow, it was centrifuged and then washed with 500 mL of 5% HCl and distilled water in sequence until the solution became neutral. The solution was then placed on the surface of a watch glass and dried to obtain a graphite oxide (oxygen atom content of 25-30 at.%) film with a thickness of 15-20 μm.

[0069] The prepared graphite oxide film was placed on the surface of a foam board floating on the water surface, the water temperature was maintained at 40°C, and the entire water tank was sealed with plastic wrap and left to stand for 1 hour to obtain a wet graphite oxide film;

[0070] (2) The wet graphite oxide film obtained in step (1) is subjected to flame plasma induction treatment, wherein the wet graphite oxide film is placed on the surface of a porous metal mesh and then moved into a flame zone. After the wet graphite oxide film changes from brown to black, the flame zone is immediately removed. The entire process takes less than 3 seconds to obtain a graphene-based electrode material.

[0071] Example 4

[0072] A method for preparing a graphene-based electrode material, comprising the following steps:

[0073] (1) Preparation of graphite oxide by Brodie method in chemical exfoliation: 2 g of graphite powder was added to 3 mL of concentrated sulfuric acid containing 3 g of K2S2O8 and 3 g of P2O5, heated at 80°C for 6 h, then cooled to room temperature, diluted with distilled water, washed to neutrality, and dried to obtain pre-oxidized graphite oxide. 1 g of the obtained pre-oxidized graphite was added to 46 mL of concentrated sulfuric acid, 3 g of potassium permanganate was added under ice-water bath conditions, and reacted at 35°C for 2 h; after the reaction, 46 mL of distilled water was added, and then 280 mL of distilled water and 5 mL of 30% hydrogen peroxide were slowly added, and the mixture was centrifuged while hot, and finally washed to neutrality with 500 mL of 5% dilute hydrochloric acid and a large amount of distilled water, and then placed on the surface of a watch glass, and dried to obtain a graphite oxide (oxygen atom content of 25-30 at.%) film with a thickness of 15-20 μm;

[0074] The prepared graphite oxide film was placed on the surface of a foam board floating on the water surface, the water temperature was maintained at 25°C, and the entire water tank was sealed with plastic wrap and left to stand for 5 hours to obtain a wet graphite oxide film;

[0075] (2) The wet graphite oxide film obtained in step (1) is subjected to flame plasma induction treatment, wherein the wet graphite oxide film is placed on the surface of a porous metal mesh and then moved into a flame zone. After the wet graphite oxide film changes from brown to black, the flame zone is immediately removed. The entire process takes less than 3 seconds to obtain a graphene-based electrode material.

[0076] Example 5

[0077] A method for preparing a graphene-based electrode material, comprising the following steps:

[0078] (1) Preparation of graphite oxide by the Hummers method of chemical exfoliation: 1 g of flake graphite and 0.5 g of sodium nitrate were weighed and placed in a 250 mL round-bottom flask, 23 mL of 98% by weight concentrated sulfuric acid was weighed and added to the round-bottom flask, a magnet was added, the round-bottom flask was placed in an ice-water bath, and stirred for 30 min, 3 g of potassium permanganate was weighed and added to the reactor, and stirring was continued for 1 h. After the reaction was completed, the reactor was transferred to a 35° C. water bath, and stirring was continued for 30 min. 50 mL of distilled water was added to the round-bottom flask, and then the round-bottom flask was transferred to an oil bath at 98°C and stirred for 15 minutes. 140 mL of distilled water and 10 mL of 30% H2O2 were added in sequence. After the reaction system finally turned bright yellow, it was centrifuged and then washed with 500 mL of 5% HCl and distilled water in sequence until the solution became neutral. The solution was then placed on the surface of a watch glass and dried to obtain a graphite oxide (oxygen atom content of 25-30 at.%) film with a thickness of 15-20 μm.

[0079] The prepared graphite oxide film was placed on the surface of a foam board floating on the water surface, the water temperature was maintained at 25°C, and the entire water tank was sealed with plastic wrap and left to stand for 1 hour to obtain a wet graphite oxide film;

[0080] (2) The wet graphite oxide film obtained in step (1) is subjected to flame plasma induction treatment, wherein the wet graphite oxide film is placed on the surface of a porous metal mesh and then moved into a flame zone. After the wet graphite oxide film changes from brown to black, the flame zone is immediately removed. The entire process takes less than 3 seconds to obtain a graphene-based electrode material.

[0081] Comparative Example 1

[0082] A method for preparing a graphene-based electrode material, comprising the following steps:

[0083] (1) Preparation of graphite oxide by the Hummers method in chemical exfoliation: 1 g of flake graphite and 0.5 g of sodium nitrate were weighed and placed in a 250 mL round-bottom flask, 23 mL of 98% by weight concentrated sulfuric acid was weighed and added to the round-bottom flask, a magnet was added, the round-bottom flask was placed in an ice-water bath, and stirred for 30 min, 3 g of potassium permanganate was weighed and added to the reactor, and stirring was continued for 1 h. After the reaction was completed, the reactor was transferred to a 35° C. water bath, and stirring was continued for 30 min. 50 mL of distilled water was weighed and added to the reactor. Distilled water was added to the round-bottom flask, and then the round-bottom flask was transferred to an oil bath at 98° C. and stirred for 15 min. 140 mL of distilled water and 10 mL of 30% H2O2 were added in sequence. After the reaction system finally turned bright yellow, it was centrifuged, and then washed with 500 mL of 5% HCl hydrochloric acid and distilled water in sequence until the solution became neutral. The solution was then placed on the surface of a watch glass and dried to obtain a graphite oxide (oxygen atom content of 25 to 30 at.%) thin film with a thickness of 15 to 20 μm, thereby obtaining a graphite oxide film.

[0084] (2) The graphite oxide film obtained in step (1) is subjected to flame plasma induction treatment, wherein the graphite oxide film is placed on the surface of a porous metal mesh and then moved into a flame zone. After the graphite oxide film changes from brown to black, the flame zone is immediately removed. The entire process takes less than 3 seconds to obtain a reduced graphene oxide powder electrode material.

[0085] Application Example 1

[0086] A method for preparing a working electrode: 2 mg of the graphene-based electrode material prepared in Example 1 is placed between two sheets of nickel foam, and pressed at a pressure of 8 MPa for 10 minutes to prepare a working electrode.

[0087] Application Example 2

[0088] A method for preparing a working electrode: 2 mg of the graphene-based electrode material prepared in Example 2 is placed between two sheets of nickel foam, and pressed at a pressure of 8 MPa for 10 minutes to prepare a working electrode.

[0089] Application Example 3

[0090] A method for preparing a working electrode: 2 mg of the graphene-based electrode material prepared in Example 3 is placed between two sheets of nickel foam, and pressed at a pressure of 8 MPa for 10 minutes to prepare a working electrode.

[0091] Application Example 4

[0092] A method for preparing a working electrode: 2 mg of the graphene-based electrode material prepared in Example 4 is placed between two sheets of nickel foam, and pressed at a pressure of 8 MPa for 10 minutes to prepare a working electrode.

[0093] Application Example 5

[0094] A method for preparing a working electrode: 2 mg of the graphene-based electrode material prepared in Example 5 is placed between two sheets of nickel foam, and pressed at a pressure of 8 MPa for 10 minutes to prepare a working electrode.

[0095] Comparative application example 1

[0096] A method for preparing a working electrode: 2 mg of the graphene-based electrode material prepared in Comparative Example 1 is placed between two sheets of nickel foam, and pressed at a pressure of 8 MPa for 10 minutes to prepare a working electrode.

[0097] Test Case

[0098] (1) Electrochemical performance test:

[0099] The working electrodes prepared in Application Examples 1 to 5 and Comparative Example 1 were respectively assembled into a three-electrode system, and their electrochemical performance was tested. The assembly method of the three-electrode system is as follows: a platinum sheet electrode is used as a counter electrode, a saturated calomel electrode is used as a reference electrode, and a 2 mol / L KOH aqueous solution is used as an electrolyte solution. The test equipment is a Shanghai Chenhua 660E electrochemical workstation; the charge transfer impedance is obtained by testing the electrochemical impedance spectrum module (AC Impedance) in the Shanghai Chenhua 660E electrochemical workstation. The specific capacitance (Cs) is tested by the constant current charge and discharge module (Chronopotentiometry) in the Shanghai Chenhua 660E electrochemical workstation, and is calculated using the formula Cs = It / mΔv, where I, t, m, and v represent the discharge current (A), discharge time (s), active material mass (g), and potential difference (V), respectively. The test results are shown in Table 1:

[0100] Table 1 Electrochemical performance test results of working electrodes prepared in Application Examples 1 to 5 and Comparative Example 1

[0101] sample Charge transfer impedance(Ω) Specific capacitance (F / g) Application Example 1 <1 245~260 Application Example 2 <1 235~243 Application Example 3 <1 240~250 Application Example 4 <1 230~240 Application Example 5 <1 265~280 Comparative Example 1 <1 180~200

[0102] (2) Morphology test

[0103] Figure 1 This is an optical photograph of the graphene-based electrode material prepared in Example 1;

[0104] Figure 2 This is a SEM image of the graphene-based electrode material prepared in Example 1;

[0105] Figure 3 This is the XPS spectrum of the graphene-based electrode material prepared in Example 1;

[0106] Figure 4 This is the Raman spectrum of the graphene-based electrode material prepared in Example 1.

[0107] Depend on Figure 1 It can be seen that the graphene-based electrode material prepared in Example 1 is a black, loose, uniform film-like material, indicating that the film-like material has been successfully prepared. Figure 2 It can be seen that the graphene-based electrode material prepared in Example 1 presents a porous mesh structure composed of wrinkled gauze at the microscopic level, indicating that the porous mesh structure has been successfully prepared. Figure 3 It can be seen that the oxygen content of the graphene-based electrode material prepared in Example 1 is relatively low. After quantitative analysis, the oxygen content is 5.8 at.%, indicating that reduced graphene oxide is obtained after the reduction treatment. Figure 4 It can be seen that the graphene-based electrode material structure prepared in Example 1 contains a large number of carbon defects, indicating that the reduced graphene oxide obtained has a large number of defect structures.

[0108] Figure 5 This is an optical photograph of the reduced graphene oxide powder electrode material prepared in Comparative Example 1;

[0109] Figure 6 This is a SEM image of the reduced graphene oxide powder electrode material prepared in Comparative Example 1;

[0110] Figure 7 This is the XPS spectrum of the reduced graphene oxide powder electrode material prepared in Comparative Example 1;

[0111] Figure 8 This is the Raman spectrum of the reduced graphene oxide powder electrode material prepared in Comparative Example 1.

[0112] Depend on Figure 5 It can be seen that the reduced graphene oxide powder electrode material prepared in Comparative Example 1 is black, loose, and powdery. Figure 6 It can be seen that the reduced graphene oxide powder electrode material prepared in Comparative Example 1 is a wrinkled gauze-like structure. Figure 7 It can be seen that the oxygen content of the reduced graphene oxide powder electrode material prepared in Comparative Example 1 is 6.2 at.%. Figure 8 It can be seen that the reduced graphene oxide powder electrode material prepared in Comparative Example 1 contains a large number of carbon defects in its structure.

[0113] Fig. 9 A constant current charge-discharge curve (GCD) of the graphene-based electrode material prepared in Example 1 at a current density of 1 A / g;

[0114] Fig.10 This is the GCD diagram of the reduced graphene oxide powder electrode material prepared in Comparative Example 1 at a current density of 1 A / g.

[0115] Depend on Fig. 9It can be seen that the GCD diagram of the graphene-based electrode material prepared in Example 1 at a current density of 1 A / g presents a charge-discharge curve that is approximately an isosceles triangle, indicating its double-layer energy storage behavior of the supercapacitor. Fig.10 It can be seen that the GCD diagram of the reduced graphene oxide powder electrode material prepared in Comparative Example 1 at a current density of 1 A / g also presents a charge and discharge curve that is approximately an isosceles triangle.

[0116] Fig.11 This is a comparison chart of the specific capacitance of the graphene-based electrode material prepared in Example 1 and the reduced graphene oxide powder electrode material prepared in Comparative Example 1. Fig.11 It can be seen that the specific capacitance of the graphene-based electrode material prepared in Example 1 is significantly stronger than that of the reduced graphene oxide powder electrode material prepared in Comparative Example 1, indicating that its energy storage capacity is stronger.

[0117] Fig.12 The electrochemical impedance spectroscopy (EIS) diagram of the graphene-based electrode material prepared in Example 1;

[0118] Fig.13 This is the EIS graph of the reduced graphene oxide powder electrode material prepared in Comparative Example 1.

[0119] Depend on Fig.12 It can be seen that the EIS graph of the graphene-based electrode material prepared in Example 1 presents a very small semicircle in the high-frequency region, indicating that its charge transfer impedance is small and its charge transfer ability is strong, which is conducive to charge exchange, thereby obtaining high electrochemical activity. Fig.13 It can be seen that the EIS graph of the reduced graphene oxide powder electrode material prepared in Comparative Example 1 also presents a very small semicircle in the high-frequency region, indicating that its charge transfer impedance is small, the charge transfer ability is strong, and it is conducive to charge exchange.

[0120] Fig.14 This is a comparison chart of the cycle life of the graphene-based electrode material prepared in Example 1 and the reduced graphene oxide powder electrode material prepared in Comparative Example 1. Fig.14 It can be seen that the cycle life of the graphene-based electrode material prepared in Example 1 is significantly better than that of the reduced graphene oxide electrode material prepared in Comparative Example 1.

[0121] It can be seen from the above test results and the accompanying drawings that the method provided by the present invention is not only simple to operate, efficient, and can be mass-produced, but also the prepared graphene-based electrode material has high activity, high specific capacitance, good conductivity, and excellent cycle performance.

[0122] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a graphene-based electrode material, comprising the following steps: (1) Wetting the graphite oxide film to obtain a wet graphite oxide film; (2) treating the wet graphite oxide film obtained in step (1) with flame plasma induction to obtain a graphene-based electrode material; The oxygen atom content of the graphite oxide in the graphite oxide film in step (1) is 25 to 30 at.%; The wetting treatment method includes: placing the graphite oxide film in a water vapor environment until the graphite oxide film absorbs water to saturation, thereby obtaining a wet graphite oxide film; The method of flame plasma induction treatment in step (2) comprises: contacting the graphite oxide film with the outer flame of the flame, and the contact time is less than 3s.

2. The method for preparing a graphene-based electrode material according to claim 1, characterized in that: The thickness of the graphite oxide film in the step (1) is 10 to 40 μm.

3. The method for preparing a graphene-based electrode material according to claim 1, characterized in that: The temperature of the water vapor environment is 25-50°C.

4. The method for preparing a graphene-based electrode material according to claim 1, characterized in that: The standing time is 0.5 to 5 hours.

5. The graphene-based electrode material prepared by the preparation method according to any one of claims 1 to 4, wherein the graphene-based electrode material has a porous network structure.

6. Use of the graphene-based electrode material according to claim 5 as a working electrode of a supercapacitor.